Metasurface‐Enabled Generation of Circularly Polarized Single Photons - Kan, Yinhui; Andersen, Sebastian K. H.; Ding, Fei; Kumar, Shailesh; Zhao, Changying; Bozhevolnyi, Sergey I. (Advanced materials (Weinheim), 2020)
Single photons carrying spin angular momentum (SAM), i.e., circularly polarized single photons generated typically by subjecting a quantum emitter (QE) to a strong magnetic field at low temperatures, are at the core of chiral quantum optics enabling nonreciprocal single‐photon configurations and deterministic spin‐photon interfaces. Here, a conceptually new approach to the room‐temperature generation of SAM‐coded single photons (SSPs) is described, which entails QE nonradiative coupling to surface plasmons being transformed, by interacting with an optical metasurface, into a collimated stream of SSPs with the designed handedness. Design, fabrication, and characterization of SSP sources, consisting of dielectric circular nanoridges with azimuthally varying widths deterministically fabricated on a dielectric‐protected silver film around a nanodiamond containing a nitrogen‐vacancy center, are reported. With properly engineered phases of QE‐originated fields scattered by nanoridges, the outcoupled photons are characterized by a well‐defined SAM (with the chirality >0.8) and high directionality (collection efficiency up to 92%). A novel approach to room‐temperature generation of circularly polarized single photons is described, which entails nonradiative coupling of a quantum emitter to surface plasmons being transformed by an optical metasurface into a collimated stream of circularly polarized single photons. Fabrication and characterization of a metasurface consisting of dielectric circular width‐gradient nanoridges fabricated on a silver film around the emitter are reported.